2013
DOI: 10.1111/imb.12072
|View full text |Cite
|
Sign up to set email alerts
|

Middle region of FancM interacts with Mhf and Rmi1 in silkworms, a species lacking the Fanconi anaemia (FA) core complex

Abstract: The Fanconi anaemia (FA) pathway is responsible for interstrand crosslink (ICL) repair. Among the FA core complex components, FANCM is believed to act as a damage sensor for the ICL-blocked replication fork and also as a molecular platform for FA core complex assembly and interaction with Bloom's syndrome (BS) complex that is thought to play an important role in the processing of DNA structures such as stalled replication forks. In the present study, we found that in silkworms, Bombyx mori, a species lacking t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 31 publications
(49 reference statements)
0
17
0
Order By: Relevance
“…Two dsRNAs targeted to different regions in PsANTI1 and PsANTI2 were generated using pLit plasmids 14) by in vitro transcription using the T7 RiboMAX large-scale RNA production kit (Promega) according to the manufacturer's protocol. Venus is a variant of the green fluorescent protein, and dsVENUS was used as a negative control.…”
Section: Double-stranded Rnasmentioning
confidence: 99%
“…Two dsRNAs targeted to different regions in PsANTI1 and PsANTI2 were generated using pLit plasmids 14) by in vitro transcription using the T7 RiboMAX large-scale RNA production kit (Promega) according to the manufacturer's protocol. Venus is a variant of the green fluorescent protein, and dsVENUS was used as a negative control.…”
Section: Double-stranded Rnasmentioning
confidence: 99%
“…Recent studies identified the histone fold complex MHF as a conserved regulator of these motor proteins (Singh et al 2010;Yan et al 2010;Lorenz et al 2012;Tao et al 2012;Yang et al 2012;Bhattacharjee et al 2013;Sugahara et al 2013;Wang et al 2013;Fox et al 2014;Zhao et al 2014). Here we provide genetic and biochemical evidence that the budding yeast MHF selectively regulates Mph1 functions to highlight the functional versatility of this family of histone fold complexes.…”
Section: Interaction With Mph1 Is Indispensable For Scmhf Functionmentioning
confidence: 99%
“…In our previous experiment in silkworms, FA proteins were required for MMC resistance, whereas Mhf and BLM complex proteins were dispensable for such resistance; these results differed from those in human cells [4,26,28,35]. The difference between silkworms and humans suggests that some DNA repair pathways function differently in response to MMC treatment in these organisms.…”
Section: Resultsmentioning
confidence: 76%
“…We previously demonstrated that FancM is required for FancD2 monoubiquitination in response to MMC treatment in BmN4‐SID1 cells [28]. To determine whether the increased levels of monoubiquitinated FancD2 induced by HU and CPT depend on the presence of the FancM protein, the ratio of monoubiquitinated to non‐ubiquitinated FancD2 was measured under silencing of FancM mediated by two dsRNAs that were previously shown to be effective in this regard [28] (Fig.…”
Section: Resultsmentioning
confidence: 99%